(3CMhGd ePgH GdGeGe CHj GdMSf GdCTYQis ((3ajVi Hf EHQGgje Hf eUWai s)
(3ChdgG (B:s
(3GdMeO ddg ChdkG hBNQkG hUdi Gddg Ydi eMeO XGgQkG hHGWfG hSde cKjQkG , CeG HYO abO hbaJ s
(3BNQgG (B:s
(3aGYdeg Ef TGA Gddg JHGQc hJYGdi , hHYOg gPG BNQ GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B6 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeYI GdeUQjI (B(22962) s
Keywords: (3GdJGQjNs